Plant-virus-insect tritrophic interactions: insights into the functions of geminivirus virion-sense strand genes. Issue 1936 (14th October 2020) - Vinoth Kumar, R.; Shivaprasad, P. V.
Abstract : The genome of the plant-infecting viruses in the family Geminiviridae is composed of one or two circular single stranded DNA of approximately 2.7–5.2 kb in length. These viruses have emerged as the most devastating pathogen infecting a large number of crops and weeds across the continents. They code for fewer open reading frames (ORFs) through the generation of overlapping transcripts derived from the bidirectional viral promoters. Members of geminiviruses code for up to four ORFs in the virion-sense strand, and their gene expression is regulated by various cis -elements located at their promoters in the intergenic region. These viral proteins perform multiple functions at every stage of the viral life cycle such as virus transport, insect-mediated virus transmission and suppression of host defence. They impede the host's multi-layered antiviral mechanisms including gene silencing (at transcriptional and post-transcriptional levels) and hypersensitive response. This review summarizes the essential role of virion-sense strand encoded proteins in transport of viral genomes within and between plant cells, countering defence in hosts (both plants and the insects), and also in the ubiquitous role in vector-mediated transmission. We highlight the significance of their pro-viral activities in manipulating host-derived innate immune responses and the interaction with whitefly-derived proteins. We also discuss the current knowledge on virus replication and transcription within the insect body.